Penegakan Hukum terhadap Kejahatan Lingkungan: Antara Kepentingan Ekonomi dan Keadilan Ekologis - M. Faisal Rahendra Lubis; Annisa Febianna Manurung; Nur Shaella Maharani; Muhammad Oriza Arifin; Felysha Azwa Tasbihta Surbakti (Lembaga Yasin AlSys, 2026)
The increasing number of environmental crime cases poses a serious challenge to achieving sustainable development in Indonesia, particularly when environmental law enforcement is confronted with the dominance of economic interests. Although environmental law enforcement has been widely studied, discussions on the dilemma between economic interests and ecological justice in the law enforcement process remain limited. This study aims to analyze the implementation of law enforcement against environmental crimes and identify obstacles arising from the dominance of economic interests. This study used a qualitative approach with a normative juridical research design through an analysis of legislation, legal literature, and relevant case studies. The results show that environmental law enforcement still faces various obstacles, including conflicts of interest, weak application of sanctions, and low political commitment to environmental protection. These findings affirm that a development orientation that overly emphasizes economic interests can weaken the principle of ecological justice and hinder the effectiveness of environmental protection. The conclusion of this study emphasizes the importance of strengthening regulations, increasing the effectiveness of law enforcement, and enhancing synergy among stakeholders to achieve ecological justice and sustainable development. The contribution of this study lies in strengthening an environmental law perspective that positions ecological justice as a basis for balancing economic interests and environmental protection.